Bestrophin1 Channels are Insensitive to Ethanol and Do not Mediate Tonic GABAergic Currents in Cerebellar Granule Cells - Diaz, Marvin R.; Wadleigh, Aya; Hughes, Benjamin A.; Woodward, John J.; Valenzuela, Carlos F. (Frontiers in Neuroscience, 2012)
The granule cell layer of the cerebellum functions in spatio-temporal encoding of information. Granule cells are tonically inhibited by spillover of GABA released from Golgi cells and this tonic inhibition is facilitated by acute ethanol. Recently it was demonstrated that a specialized Ca2+-activated anion channel, bestrophin1 (Best1), found on glial cells, can release GABA that contributes up to 50-75% of the tonic GABAergic current. However, it is unknown if ethanol has any actions on Best1 function. Using whole-cell electrophysiology, we found that recombinant Best1 channels expressed in HEK-293 cells were insensitive to 80 mM ethanol. We attempted to measure the Best1-mediated component of the tonic current in slices using 5‐nitro‐2‐(3‐phenylpropylamino)benzoic acid (NPPB) (previously reported to block Best1) but, unexpectedly, found a significant potentiation of the tonic current and the area and decay of GABAA-mediated spontaneous inhibitory postsynaptic currents (IPSCs) in rats and mice under two different recording conditions. To better isolate the Best1-dependent tonic current component, we blocked the Golgi cell component of the tonic current with tetrodotoxin and found that NPPB similarly and significantly potentiated the tonic current amplitude and decay time of miniature IPSCs. Two other Cl--channel blockers were also tested: 4′‐diisothiocyanatostilbene‐2,2′‐disulfonic acid disodium salt hydrate (DIDS) showed no effect on GABAergic transmission, while niflumic acid (NFA) significantly suppressed the tonic current noise, as well as the mIPSC frequency, amplitude, and area. These data suggest that acute ethanol exposure does not modulate Best1 channels and they serve to challenge recent data indicating that these channels participate in the generation of tonic GABAergic currents in cerebellar granule cells.